Leptospirosis - Rampengan, Novie H. (UNIVERSITAS SAM RATULANGI, 2016)
Abstract: Leptospirosis is a zoonotic disease that usually occurs during the flood and is generally transmitted through rat urine. Indonesia is a country with a moderate risk of transmission of leptospirosis. Leptospirosis has a broad manifestation varying from self-limited to severe disease. The gold standard examination of leptospirosis is microscopic agglutination test. Diagnosis is divided into suspected, probable, and confirmed. Treatment consists of antibiotics and supportive agents. Generally, the prognosis is good, albeit, sequelae can occur. Case-fatality rate in different parts of the world ranging from less than 5% to 30%.Keywords: leptospirosis, diagnosis,Abstrak: Leptospirosis merupakan penyakit zoonosis yang umumnya timbul saat banjir dan umumnya ditularkan melalui kencing tikus. Indonesia merupakan negara dengan risiko sedang penularan leptospirosis. Leptospirosis memiliki manifestasi luas dari self limited hingga sakit berat. Pemeriksaan baku emas leptospirosis ialah dengan microscopic agglutination test. Diagnosis dibagi atas suspek, probable, dan konfirmasi. Terapi diberikan medikamentosa dengan antibiotik dan suportif. Prognosis umumnya baik namun bisa juga terjadi gejala sisa. Tingkat fatalitas kasus di berbagai belahan dunia berkisar <5%-30%.Kata kunci: leptospirosis, diagnosis